Business elites, the social issue and corporate social responsibility in Brazil and Argentina - Oliveira, Luciana; Dulci, Otávio (Organicom, 2013)
In this article one attempts to understand why it was the business people who assumed the dissemination of discourses and practices of corporate social responsibilty (CSR) in Brazil, while it was the civil society that accomplished this in Argentina. Thus, besides the comparative effort – always useful in pointing out similarities, differences, creating scales and perceiving generalities –, one understands that there is a gap in addressing the issue that needs to be deleted: the construction of a historical milestone for the business action in relation to the social issue. As a corollary, one intends to understand the contextual framework of meaning that encompasses the term CSR in each national situation analyzed, by taking into account the fact that albeit being a global discourse it is not homogeneous.